Reliability evaluation of a wind-diesel-battery hybrid power system - Liu, X.; Islam, Syed; Chowdhury, A.; Koval, D. (2008)
The paper presents a novel analytical approach of reliability evaluation for wind-diesel hybrid power system with battery bank for power supply in remote areas. The proposed approach is developed on the basis of the discrete wind speed frame analysis of the Weibull wind speed distribution. By employing wind speed frame analysis, an analytical model of wind-diesel hybrid system is developed that deals with system outage as a result of component failure and wind speed fluctuation. This model computes power output of wind turbine generators for each discrete wind speed frame, which is created by splitting the Weibull wind speed distribution curve. Then a model of battery bank is combined with that of the wind-diesel system. The reliability analysis of the overall system is conducted by combining power outputs of the wind and diesel generation units with battery throughout all wind speed frames to obtain the reliability indices, Loss of Load Probability (LOLP) and Expected Energy Not Supplied (EENS), which reflect a long term performance of the hybrid power system. By employing the wind speed frame the intermittent characteristics of wind speed and turbine failure can be easily taken into account. Simultaneously the modeling process can be greatly simplified and the calculation time can be saved as well. This model is suitable for system reliability assessment for both system planning and system optimization.